2015
DOI: 10.1007/s12144-015-9398-7
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Distress Associated with Surgical Treatment and its Relationship with Coping Profiles Among Chronically ill Older Patients

Abstract: The study determines the patterns of coping styles among older patients with hip osteoarthritis and assesses the derived profiles in terms of perceived stress and anxiety before and after arthroplasty. Sixty-one hospital patients (mean age 70.3 years) were analysed one day before arthroplasty and three months after. The participants were assessed with the Brief-COPE (coping style), PSS-10 (perceived stress) and STAI (anxiety) psychometric tests. Four coping patterns were yielded using data clustering: rational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
0
3
0
1
Order By: Relevance
“…Doron et al (2015), for example, identified four coping profiles among college students: high copers, adaptive copers, avoidant copers, and low copers. A few studies have measured coping in samples facing elevated levels of stress, such as cancer survivors (Hamilton, Agarwal, Carter, & Crandell, 2011), young adults at risk for substance abuse (Wong et al, 2013), adults facing heightened levels of work-related stress (Astvik & Melin, 2013), and older chronically ill patients (Stecz, Wrzesinska, Tabala, & Nowakowska-Domagala, 2017). These profiles may be more informative than general coping scales because they capture the multidimensionality of coping and indicate that the level and combination of strategies is linked with numerous psychosocial outcomes.…”
mentioning
confidence: 99%
“…Doron et al (2015), for example, identified four coping profiles among college students: high copers, adaptive copers, avoidant copers, and low copers. A few studies have measured coping in samples facing elevated levels of stress, such as cancer survivors (Hamilton, Agarwal, Carter, & Crandell, 2011), young adults at risk for substance abuse (Wong et al, 2013), adults facing heightened levels of work-related stress (Astvik & Melin, 2013), and older chronically ill patients (Stecz, Wrzesinska, Tabala, & Nowakowska-Domagala, 2017). These profiles may be more informative than general coping scales because they capture the multidimensionality of coping and indicate that the level and combination of strategies is linked with numerous psychosocial outcomes.…”
mentioning
confidence: 99%
“…22 Moreover, adaptations in the home, environmental aids, and assistive technology, as mentioned by participants in this study, may help prevent hospital admissions in patients with dementia 23 and patients with a clinical diagnosis of stroke. 24 Acceptance was an important coping strategy to participants in this study, and in the literature less acceptance and high avoidance behaviour have been associated with: readmission of patients with ischaemic heart disease; 25 significantly higher anxiety and stress levels in chronically ill older patients; 26 and greater anxiety and depression in patients living with the risk of serious arrhythmias and sudden cardiac death. 27 Moreover, positivity was used by some patients in this study to cope with their health and positive thinking has been found to be used by the majority of patients before cardiac surgery.…”
Section: Comparison With Existing Literaturementioning
confidence: 61%
“…Quanto às estratégias de enfrentamento utilizadas, coping defensivo/ evitativo foi associado a pior saúde mental (KALTSOLDA et al, 2011) e pior funcionamento físico (EISENBERG et al, 2012). Baixo enfrentamento ativo e alto comportamento evitativo apresentaram significativamente maiores indicadores de estresse e ansiedade (STECZ et al, 2017), enquanto enfrentamento com foco no problema foi vinculado à melhor aceitação da doença (JANOWSKI, STEUDEN e KURYLOWICZ, 2010). Em estudo de Panasiti et al (2019), pacientes apresentaram menor habilidade de regulação emocional em comparação ao grupo controle e também se beneficiaram mais de intervenções com estratégias cognitivas de enfrentamento.…”
Section: Lidando Com O Adoecimentounclassified